Liposome-Encapsulated Human Immunodeficiency Virus-1 gp120 Induces Potent V1V2-Specific Antibodies in Humans. (9th June 2018) - Rao, Mangala; Onkar, Sayali; Peachman, Kristina K; White, Yohann; Trinh, Hung V; Jobe, Ousman; Zhou, Yingjun; Dawson, Peter; Eller, Michael A; Matyas, Gary R; Alving, Carl R
Abstract : The AVEG015 study highlights the importance of the inclusion of 2 adjuvants in the vaccine formulation. Incorporation of aluminum hydroxide and liposomal MPL induced robust and durable gp120 and gp70V1V2 IgG binding antibodies and ADCC and α4 β7 -integrin receptor-inhibiting functional antibodies. Abstract: Background: In the RV144 trial, human immunodeficiency virus (HIV)-1 gp120 V1V2 antibodies correlated inversely with risk of HIV-1 infection; however, the titers waned quickly. We hypothesized that a more potent adjuvant might enhance the magnitude and durability of V1V2 antibodies. Methods: We examined archived sera from a phase I randomized, double-blind placebo-controlled trial, conducted in HIV-1-uninfected individuals, vaccinated with HIV-1SF-2 rgp120 either adsorbed to aluminum hydroxide (aluminum hydroxide arm) or encapsulated in liposomes containing monophosphoryl lipid A (MPL®) and then adsorbed to aluminum hydroxide (liposomal arm). Results: The median immunoglobulin G antibody titers across weeks 10–112 were higher in the liposomal arm against subtypes B (2- to 16-fold), AE (4- to 8-fold), and C (4- to 16-fold) V1V2 proteins. High titers were maintained even at 10 months after last boost in the liposomal compared with the aluminum hydroxide arm. The antibodies exhibited antibody-dependent cellular cytotoxicity (ADCC) and α4β7-integrin receptor inhibition-binding functions. Conclusions: Inclusion of 2 adjuvants in the vaccine formulation, aluminum hydroxide, and liposomal MPL®, induced robust, durable, and functional antibodies. Based on the magnitude of antibody responses and the percentage of coiled and β-sheet in the predicted V2/V3-peptide structure, we speculate that liposomal gp120 was presented in a conformation that favored the induction of robust antibody responses.